Age of faith - Fremantle, Anne J. 1909-2002 (Great ages of man., 1965)
An exciting and colorful panorama of the Middle Ages covering feudalism; the importance of religion in everyday life, culture, and art; urban life and the guilds; and knighthood and romance.